2009
DOI: 10.1262/jrd.20219
|View full text |Cite
|
Sign up to set email alerts
|

Successful Piglet Production in a Chemically Defined System for In-vitro Production of Porcine Embryos: Dibutyryl Cyclic AMP and Epidermal Growth Factor-family Peptides Support In-vitro Maturation of Oocytes in the Absence of Gonadotropins

Abstract: Abstract.To induce meiotic resumption of porcine oocytes, it is thought to be necessary to expose the cumulus-oocyte complexes (COCs) to gonadotropins during in-vitro maturation (IVM). However, the detailed mechanism of meiotic resumption by gonadotropins is still unknown, and successful piglet production has not been reported by using oocytes matured in gonadotropin-free media and fertilized in vitro. The present study was undertaken to examine the combinational effects of epidermal growth factor (EGF)-family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 45 publications
(71 reference statements)
2
37
0
1
Order By: Relevance
“…Consequently, the differences between FSH and the EGF-like peptides in stimulating maturation to MII stage may reflect the relative degree of meiotic resumption. Correspondingly with the results of our study, the EGF-like peptides were shown to stimulate maturation of pig COCs in vitro but they were less efficient than gonadotropins (eCGChCG; Akaki et al 2009). A reason of the lower potential of the EGF-like peptides to initiate resumption of meiosis in isolated pig COCs cannot be specified yet due to incomplete information about mechanisms involved in this process.…”
Section: Effect Of Egf-like Peptides On Pig Cocssupporting
confidence: 72%
See 2 more Smart Citations
“…Consequently, the differences between FSH and the EGF-like peptides in stimulating maturation to MII stage may reflect the relative degree of meiotic resumption. Correspondingly with the results of our study, the EGF-like peptides were shown to stimulate maturation of pig COCs in vitro but they were less efficient than gonadotropins (eCGChCG; Akaki et al 2009). A reason of the lower potential of the EGF-like peptides to initiate resumption of meiosis in isolated pig COCs cannot be specified yet due to incomplete information about mechanisms involved in this process.…”
Section: Effect Of Egf-like Peptides On Pig Cocssupporting
confidence: 72%
“…We assume that the reason may lie in low level of cAMP in the AREG-and EREG-stimulated COCs, which may adversely affect function of the cumulus cells and also communication between the oocyte and the cumulus compartment. This assumption is supported by the finding that combination of the EGF-like peptides with dbcAMP during first 20 h of culture improved the results of maturation to the level observed with gonadotropins and IVF, and culture of such oocytes yielded blastocysts with full developmental competence (Akaki et al 2009). In mouse preantral follicle culture model, EREG-induced incomplete mucification and expansion of the cumulus cells had a significantly lower effect than hCG/EGF on meiotic resumption and progesterone production (Romero & Smitz 2009).…”
Section: Effect Of Egf-like Peptides On Pig Cocsmentioning
confidence: 84%
See 1 more Smart Citation
“…The EGF-like peptides are also produced in cumulus cells of in vitro cultured cumulus-oocyte complexes (COCs) upon stimulation by FSH and trigger resumption of meiosis (Downs & Chen 2008). The data published by our and other laboratories strongly suggest that similar mechanisms work also in large animal species (Prochazka et al 2000, Akaki et al 2009, Yamashita et al 2009. We have recently shown that FSH induces expression of AREG and EREG but not BTC in cultured pig COCs and that these peptides stimulate expansion of cumulus cells, maturation of oocyte, and acquisition of the oocyte developmental competence.…”
Section: Introductionmentioning
confidence: 62%
“…Although many piglets have been produced following IVM, in vitro fertilization (IVF) and in vitro culture (IVC) [2,3], the quality of embryos produced in vitro is still poor, and the developmental competence remains an area requiring further research [3,4]. Furthermore, a successful IVM-IVF-IVC system utilizing chemically defined media has been recently developed to produce blastocysts and piglets [5,6]. Development of an efficient system for in-vitro production of embryos in chemically defined media would have an advantage in research to clarify the mechanism or effects of various materials during IVM, IVF and/or IVC.…”
mentioning
confidence: 99%